2019
DOI: 10.1016/j.neuron.2019.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Input-Specific Metaplasticity in the Visual Cortex Requires Homer1a-Mediated mGluR5 Signaling

Abstract: Effective sensory processing depends on sensory experience-dependent metaplasticity, which allows homeostatic maintenance of neural network activity and preserves feature selectivity. Following a strong increase in sensory drive, plasticity mechanisms that decrease the strength of excitatory synapses are preferentially engaged to maintain stability in neural networks. Such adaptation has been demonstrated in various model systems, including mouse primary visual cortex (V1), where excitatory synapses on layer 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 71 publications
3
34
0
Order By: Relevance
“…Mechanistically, scaling up and down are not the reverse of each other, but rely on distinct molecular signaling. In V1, upscaling of mEPSCs after DE correlates with phosphorylation of GluA1 on S845, synaptic appearance of Ca 2+ -permeable AMPARs (Goel et al, 2006), and mGluR1 (Chokshi et al, 2019), while downscaling is dependent on Arc (Gao et al, 2010), mGluR5, and Homer1a (Chokshi et al, 2019). Although GluA1-S845 is necessary for upscaling, it alone is not sufficient to recapitulate multiplicative scaling (Goel et al, 2011).…”
Section: Demonstration Of Homeostatic Synaptic Plasticity In Vivomentioning
confidence: 99%
See 2 more Smart Citations
“…Mechanistically, scaling up and down are not the reverse of each other, but rely on distinct molecular signaling. In V1, upscaling of mEPSCs after DE correlates with phosphorylation of GluA1 on S845, synaptic appearance of Ca 2+ -permeable AMPARs (Goel et al, 2006), and mGluR1 (Chokshi et al, 2019), while downscaling is dependent on Arc (Gao et al, 2010), mGluR5, and Homer1a (Chokshi et al, 2019). Although GluA1-S845 is necessary for upscaling, it alone is not sufficient to recapitulate multiplicative scaling (Goel et al, 2011).…”
Section: Demonstration Of Homeostatic Synaptic Plasticity In Vivomentioning
confidence: 99%
“…Consistent with this interpretation, we reported that DE-induced upscaling of mEPSCs reflects potentiation of lateral intracortical (IC) synapses, but feedforward (FF) synapses from L4 to L2/3 are immune to this type of plasticity (Petrus et al, 2015). Similarly, downscaling of mEPSCs with visual experience is also limited to IC synapses (Chokshi et al, 2019). Such input-specific synaptic scaling is observed in L5 of V1 at the level of dendritic spine plasticity.…”
Section: Demonstration Of Homeostatic Synaptic Plasticity In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…This would favor the long-term expression of the initiated plasticity. These molecular dynamics at synapses explain reported roles of mGlu5-Homer in metaplasticity (37)(38)(39). Importantly, all these studies report Homer1a as the dominant-negative IEG breaking mGlu5-Homer interaction to allow synaptic plasticity.…”
mentioning
confidence: 56%
“…In addition to inducing Hebbian plasticity, alterations in visual experience produce homeostatic plasticity of excitatory synapses in primary visual cortex (V1) of rodents (Kirkwood and Bear, 1994;Kirkwood et al, 1996;Desai et al, 2002;Goel et al, 2006;Keck et al, 2013). Specifically, in L2/3 neurons, removal of visually-driven activity by dark-exposure (DE) increases the amplitude of miniature excitatory postsynaptic currents (mEPSCs), while re-exposing DE mice to light for 2 h (LE) is sufficient to reduce mEPSC amplitudes to basal levels (Goel and Lee, 2007;Gao et al, 2010;Petrus et al, 2014;Chokshi et al, 2019). Mechanistically, the bidirectional homeostatic adaptation of excitatory synaptic strength in V1 is mediated by regulation of αamino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor function (Goel et al, 2011).…”
Section: Introductionmentioning
confidence: 99%